Schisandra chinensis alleviates Hypertriglyceridemia in nonalcoholic fatty liver disease by modulating the gut microbiota and hepatic lipid metabolism: identification of its active fractions - Li, Qi; Feng, Mei; luo, Qi; Ye, Chen Yalin; Luo, Yi Ke; Xu, Ling Yu (Frontiers in Pharmacology, 2026)
BackgroundNonalcoholic fatty liver disease (NAFLD) is a prevalent metabolic disorder characterized by hepatic lipid accumulation and gut microbiota dysbiosis. Schisandra chinensis (Turcz.) Baill. (SCH), a traditional hepatoprotective herb, has shown therapeutic potential; however, its mechanisms in NAFLD remain incompletely understood.ObjectiveTo investigate the protective effects and underlying mechanisms of SCH against NAFLD through integrated genetic, experimental, and multi-omics approaches.MethodsMendelian randomization (MR) analysis based on large-scale genome-wide association study (GWAS) datasets was performed to evaluate the causal effects of lipid traits on NAFLD risk. An HFD-induced NAFLD mouse model was used to assess the therapeutic efficacy of SCH extract, with evaluations of serum lipid profiles, liver function, and histopathology. Multi-omics analyses—including 16S rRNA sequencing, untargeted lipidomics, and hepatic metabolite profiling (LC-MS/MS)—were integrated with network pharmacology to predict active metabolite–target–pathway interactions. In vitro, an FFA-induced HepG2 steatosis model was used to screen the bioactive fractions of SCH.ResultsSCH significantly reduced hepatic TG accumulation and improved serum lipid profiles. MR analysis confirmed TG as a causal factor for NAFLD. SCH intervention enriched beneficial taxa (e.g., Turicibacter, Muribaculaceae) while suppressing HFD-induced dysbiosis. Lipidomics revealed modulation of glycerophospholipid and choline metabolism. Key phytometabolites (e.g., schisandrin B, gomisin N) were correlated with microbial composition and lipid remodeling. Network pharmacology identified putative targets involved in lipid metabolism, inflammation, and neuroendocrine signaling (e.g., PTGS2, GABRA1, ESR1). GO and KEGG enrichment supported roles in oxidative stress, steroid hormone signaling, and GABAergic synapse pathways, consistent with experimental multi-omics results. In vitro assays demonstrated that the n-butanol (BuOH) fraction was the principal bioactive component, significantly reducing lipid accumulation in HepG2 cells.ConclusionThis integrative study demonstrates that SCH protects against NAFLD by lowering triglycerides, remodeling the gut–liver axis, and reprogramming hepatic lipid metabolism. The BuOH fraction constitutes the main active component, supporting SCH as a promising multi-target candidate for NAFLD therapy.